M-Commerce And Its Legal Issues - Lee, King Kong (2005)
This research will be carried out in a way of literature reviews and analyzing the relevant laws in Malaysia. Cyber Law in United States of America will be used as reference point since they are at the advanced stage of enforcing Cyber Law. Based on the United States legal experience, Malaysian perspective will be re-visited. The scope will be limited to specific issues related to m-commerce.